Implementation of The Quantum Paradigm For Policy Studies in Indonesia - Abdul Rahman (Public Policy Journal, 2026)
This research aims to analyze the potential implementation of the quantum paradigm as an alternative analytical framework in public policy studies in Indonesia. The research is motivated by the limitations of the classical/conventional policy paradigm, which tends to be deterministic and linear in its understanding of the uncertainty and complexity of policies in Indonesia. Through qualitative methods with literature study techniques, this paper critically examines the development of policy theory—from the rational-comprehensive model, incrementalism, to complexity-based theory—and identifies theoretical gaps that can be filled by a quantum approach. The quantum paradigm, with the concepts of superposition, entanglement, and interference, is offered not merely as an analogy but as a mathematical-conceptual foundation for modeling the contextual nature of preferences, non-linear relationships between issues, and the role of measurement in the policy process. The research results formulate a framework of 3 components that can be operationalized: 1) Quantum Stakeholder Preference Mapping; 2) Linkage Analysis for Policy Integration, and 3) Policy Window Modeling as Resonance. This study concludes that the quantum paradigm offers a more sophisticated and contextual way to understand and navigate Indonesia's plural and interconnected policy realities, while opening up opportunities to enhance the effectiveness, legitimacy, and resilience of policy governance.